Serial Fetal MRI for the Diagnosis of Aicardi Syndrome. Issue 4 (August 2013) - Hergan, B.; Atar, O.D.; Poretti, A.; Huisman, T.A.G.M.
Aicardi syndrome (AS) is defined by the triad of corpus callosum agenesis, chorioretinal "lacunae" and infantile spasms. Additional neuroimaging findings including migrational abnormalities are common. We report on serial neuroimaging findings of a female fetus with ventriculomegaly, corpus callosum agenesis and focal migrational abnormalities, suggestive of AS. Postnatal neuroimaging follow-up as well as ophthalmological evaluation and occurrence of infantile spasms confirmed the prenatally suspected diagnosis of AS. This case points out the key role of serial fetal magnetic resonance imaging (MRI) in detecting the full spectrum of pathologies associated with fetal ventriculomegaly. The associated neuroimaging findings may go undetected on prenatal ultrasound, but are important in terms of diagnosis and counseling of the parents. Additionally, this case emphasizes the importance of serial fetal MRI studies to more accurately delineate the progression of findings during brain development.